Cheetah math : learning about division from baby cheetahs - Nagda, Ann Whitehead, 1945-; San Diego Zoo. (New York : Holt, 2007)
Uses information about the cheetahs who live in the San Diego Zoo to teach children about division.
Kirkus Review
5.3
3-6
3-6
Keywords: Cheetah -- Pictorial works -- Juvenile literature; Division -- Juvenile literature; Cheetah; Division; Cheetahs; Division